Pengaruh Pendidikan Agama Islam Terhadap Akhlak Siswa: Studi Kasus di SDN 009 Nunukan - Dedi Gunawan Saputra (Yayasan Syamil Quran Nunukan, 2025)
Islamic Religious Education (PAI) has an important role in shaping students' morals, especially in elementary schools. This study aims to analyze the relationship between Islamic Religious Education learning and students' morals at SDN 009 Sungai Fatimah, Nunukan Regency. The research method used is quantitative with a correlation approach, involving 30 students as randomly selected samples. Data were collected through questionnaires and analyzed using the product moment correlation technique. The results of the study indicate that Islamic Religious Education learning in this school has been adjusted to the curriculum and school conditions, with varied teaching methods such as lectures, discussions, and questions and answers. Evaluation is carried out through cognitive, affective, and psychomotor aspects. Efforts to shape students' morals are implemented through teacher role models and positive behavioral habits, such as congregational prayer, saving, giving alms, and respecting teachers. Data analysis shows that the majority of students have good morals, which are reflected in their habits of worship, social concern, cleanliness, and respect for teachers and parents. In addition, there is a positive correlation between students' morals and their academic achievement in Islamic Religious Education subjects. The better the students' morals, the better their learning outcomes. This finding confirms that religious education plays a significant role in shaping the character of students who are noble and achieve.